Evidence for an anomalous like-sign dimuon charge asymmetry - Abazov, V. M. (2010)
We measure the charge asymmetry A=(N++-N-)/(N +++N-) of like-sign dimuon events in 6.1fb-1 of pp̄ collisions recorded with the D0 detector at a center-of-mass energy √s=1.96TeV at the Fermilab Tevatron collider. From A we extract the like-sign dimuon charge asymmetry in semileptonic b-hadron decays: Aslb=-0.00957±0.00251(stat)±0.00146(sys). It differs by 3.2 standard deviations from the standard model prediction Aslb(SM)=(-2.3-0.6+0.5) ×10-4, and provides first evidence of anomalous CP violation in the mixing of neutral B mesons.